Las TIC como herramienta en el proceso de enseñanza-aprendizaje en los estudiantes del 7º año de la Unidad Educativa Toacaso cantón Latacunga - Zumba Pila, Mayra Alexandra (2021)
The development of this research study with the topic "ICT as innovative tools in the teaching-learning process" has been proposed and carried out in order to solve the problem of how to improve the teaching-learning process with the use of ICT. Therefore, it seeks to implement strategies in the use of ICT in teaching-learning process as a tool for educational management; a theoretical and scientific foundation focus on the research study was required, thus it was also necessary to determine the current situation of the educational Unit regarding the study variables, to implement methodological strategies based on the use of ICT and subsequently validate the proposal by the system of specialists. Methodologically, it has been based on a mixed, approach, under the applied modality with the support of both inductive and deductive methods. In addition, the questionnaire technique has been used. All the work has allowed to conclude that the validation process of the proposal has been carried out with the support of 4 specialists and 26 users who after analyzing the document and each of the strategies implemented for the work in each classroom considers placing it at an excellent level, which guarantees the work performed to solve the identified problem